PAKEM APPLICATION IN FIQIH LEARNING AT MIN 46 ACEH BESAR - Sofia, Ana; Azmi, Ulil; Trisnawati, Trisnawati (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
This research is motivated by the implementation of PAKEM in Fiqh Learning at MIN 46 Aceh Besar starting from the need to improve the quality of Fiqh learning, which so far still often uses conventional methods such as lectures. This method often makes students passive and less actively involved in the learning process, so that understanding of Fiqh material is less than optimal. The PAKEM method (Active, Creative, Effective, and Enjoyable Learning) was introduced to create more interactive learning and involve students in the learning process more actively. The method used in the study is to use a qualitative approach with the type of field research. The research results show that: 1). The effectiveness of the application of the PAKEM method in Fiqh learning at MIN 46 Aceh Besar is that the application of the PAKEM method in Fiqh learning at MIN 46 Aceh Besar is very effective in improving the quality of learning. Students become more active, creative, and enjoy the learning process. 2). Supporting and inhibiting factors in the implementation of the PAKEM method in Fiqh learning at MIN 46 Aceh Besar are that there are several challenges, such as differences in student abilities and limited facilities, the implementation of PAKEM still has a significant positive impact on student learning outcomes.